Analysis of optical emission spectroscopy data during silicon etching in SF6/O2/Ar plasma. (12th October 2021) - KIM, Dong Hwan; CHOI, Jeong Eun; HONG, Sang Jeen
Abstract: Silicon etching is an essential process in various applications, and a major challenge for etching process is anisotropic high aspect ratio etching characteristics. The etch profile is determined by the plasma parameters and process parameters. In this study, the plasma state with each process parameters were analyzed through the optical emission spectroscopy (OES) plasma diagnostic sensor by both chemical and physical approaches. Electron temperature and electron density were additionally acquired using the corona model with OES data that provides chemical species information, and the etch profile was evaluated through scanning electron microscope measurement data. The results include changes in profile with gas ratio, bias power, and pressure. We figure out that factors like ion energy and ion angular distribution as well as chemical reaction affect the anisotropic profile.